2020
DOI: 10.1016/j.jhsa.2019.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Reoperation and Conversion to Wrist Fusion After Proximal Row Carpectomy or 4-Corner Arthrodesis

Abstract: Purpose Proximal row carpectomy (PRC) and 4-corner arthrodesis (FCA) are common salvage procedures for the treatment of scapholunate advanced collapse and scaphoid nonunion advanced collapse. This study aimed to assess rates of reoperation and conversion to wrist fusion and to assess the factors associated with reoperation and conversion to wrist fusion for patients treated with PRC and FCA.Methods A retrospective chart review was performed evaluating 266 adult patients undergoing PRC or FCA at a single instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…35 Additionally, Wagner et al 18 reported similar 10-year total wrist arthrodesis-free and revision-free intervals for both PRC (84% and 81%, respectively) and 4-CF (88% and 80%, respectively). 18 However, these findings were contradicted by a recent study by van Hernan et al, 36 which reported higher revision rates in patients treated with 4-CF compared with those treated with PRC.…”
Section: Discussionmentioning
confidence: 92%
“…35 Additionally, Wagner et al 18 reported similar 10-year total wrist arthrodesis-free and revision-free intervals for both PRC (84% and 81%, respectively) and 4-CF (88% and 80%, respectively). 18 However, these findings were contradicted by a recent study by van Hernan et al, 36 which reported higher revision rates in patients treated with 4-CF compared with those treated with PRC.…”
Section: Discussionmentioning
confidence: 92%
“…7 38 With similar results between conventional outcomes, attention has been turned to other outcome measures to establish which technique provides optimal treatment. Proximal row carpectomy has been reported to have a better patient-reported outcomes ( Table 5 ), 39 lower complications, 38 less secondary procedures, 36 40 and less conversion to total wrist arthrodesis, 41 though this remains controversial. 36 40 Studies also indicate that PRC also has a cost benefit, 42 while generating lower direct costs to patients.…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, a secondary radial styloidectomy was performed in eight out of 47 patients (17%). Van Hernen et al., (2020) investigated factors associated with reoperation after PRC and four-corner arthrodesis and found that a primary radial styloidectomy was performed in 66 of the 266 patients following both procedures. During follow-up, a wrist arthrodesis was not performed in any of the patients with a primary radial styloidectomy, while 20 of the 200 patients without primary radial styloidectomy required a secondary wrist fusion.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of wrist arthrodesis after PRC is well described, with incidences between 5% and 24% (Chedal-Bornu et al, 2017;Garcia et al, 2020;Kay et al, 2020;van Hernen et al, 2020;Williams et al, 2018). Less is known about secondary radial styloidectomy after PRC; Imbriglia et al (1990) performed a secondary radial styloidectomy in two out of 27 patients (7%).…”
Section: Discussionmentioning
confidence: 99%